2017
DOI: 10.1038/srep42746
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial behaviour throughout the lytic cycle of Toxoplasma gondii

Abstract: Mitochondria distribution in cells controls cellular physiology in health and disease. Here we describe the mitochondrial morphology and positioning found in the different stages of the lytic cycle of the eukaryotic single-cell parasite Toxoplasma gondii. The lytic cycle, driven by the tachyzoite life stage, is responsible for acute toxoplasmosis. It is known that whilst inside a host cell the tachyzoite maintains its single mitochondrion at its periphery. We found that upon parasite transition from the host c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(118 citation statements)
references
References 48 publications
(62 reference statements)
13
105
0
Order By: Relevance
“…In model organisms, mitochondrial morphology and function are tightly linked. In support of this also being the case in Toxoplasma, recent studies reported rapid mitochondrial remodelling in respond to drastic changes in the growth environments (Charvat and Arrizabalaga, 2016;Ovciarikova et al, 2017). The morphological defect observed here upon TgmS35 depletion provides additional support (Fig.…”
Section: Mitochondrial Morphology Captured By Immunofluorescence Is Lsupporting
confidence: 87%
See 2 more Smart Citations
“…In model organisms, mitochondrial morphology and function are tightly linked. In support of this also being the case in Toxoplasma, recent studies reported rapid mitochondrial remodelling in respond to drastic changes in the growth environments (Charvat and Arrizabalaga, 2016;Ovciarikova et al, 2017). The morphological defect observed here upon TgmS35 depletion provides additional support (Fig.…”
Section: Mitochondrial Morphology Captured By Immunofluorescence Is Lsupporting
confidence: 87%
“…Ke et al, 2018;Seidi et al, 2018) and on fluorescence microscopy analysis using fluorescent dyes (e.g. Vercesi et al, 1998;Garbuz and Arrizabalaga, 2017;Ovciarikova et al, 2017) for mitochondrial functional studies. Here, we developed an organelle enrichment protocol which generates high-quantity fractions enriched with active mitochondria that can be used to investigate the activity of mitochondrial pathways in vitro.…”
Section: A New Protocol To Follow Mitochondrial Translation In T Gondiimentioning
confidence: 99%
See 1 more Smart Citation
“…During this process, specialized secretory organelles (dense granules, micronemes, and rhoptries) are synthesized de novo from the Golgi within the forming daughter cells. Finally, the single mitochondrion from the mother enters each developing daughter parasite (Ovciarikova et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…more plausible, since it is not unusual for apicomplexan parasites. For example, the morphology of Toxoplasma mitochondria changes radically during the transition of the parasite from the host cell to the extracellular matrix (Ovciarikova et al 2017). The mitochondria of Plasmodium falciparum grow from single, small, discrete organelles into highly branched structures in the later stages of its life cycle (van Dooren et al 2005).…”
Section: Discussionmentioning
confidence: 99%